Education on Eye Ointments and Eye Drops for the Elderly at the Gedang Hanyar Health Center - Setiawan, Deni; Fatimatuz Zahra; Khairunnisa; Ade Syarif Hakim; Satrio Wibowo Rahmatullah; Dita Ayulia Dwi Sandi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Eye drops and eye ointment are sterile drugs used to treat eye disorders. Using eye medications without using the instructions correctly can cause harm to the eyes. Elderly is a stage of life marked by a decrease in physical abilities including memory, so that it requires attention, especially in the use of special drugs. The purpose of this activity is to promote health regarding the use of eye drops and ointments targeting the elderly in the Gadang Hanyar Health Center area. Education is carried out through lectures with the help of leaflets. The target of the activity is elderly patients who are being treated at the Puskesmas during the activity. The results of the pretest showed that the patient's knowledge in general was good which was marked with a value of more than 70. The posttest was carried out after education using leaflets showed an increase in the knowledge value of ± 12-15 points from the initial value. Education on eye ointment and eye drops using leaflets significantly increases the knowledge of elderly respondents.